Effects of tourniquet use in paediatric lower leg surgery. (2020) - Hanna, Rewais B.; Nies, Matthew; Lang, Pamela J.; Halanski, Matthew
Abstract: Background: The purpose of this study is to evaluate the use of the tourniquet and its effect on post-operative pain in the paediatric population following lower leg procedures. Methods: A retrospective study of paediatric patients (under the age of 18) undergoing inpatient orthopaedic procedure below the knee performed at a single academic institution between 1st December 2013 and 31st January 2019 was conducted. Primary outcome measures of total opioid consumption during hospital stay and pre-operative nerve block utilization were retrieved from the electronic medical record (EMR). Secondary outcome measures of blood loss, tourniquet time, procedure time and length of hospital stay were also retrieved. Student's t-tests were used to assess statistical significance between two sample means. Results: The final analysis included 204 paediatric procedures, 118 of which used a tourniquet and 86 of which did not. Paediatric patients with a tourniquet had significantly more opioid consumption post-operatively in the form of weight-based morphine equivalents/length of stay (p = 0.01) compared to those who had no tourniquet. This held true for males (p = 0.049) and females (p = 0.04) respectively. We did not see an increase in wound complications or return trips to the operating room in the tourniquet cohort. All procedures included an osseous component except one procedure in the non-tourniquet group. Conclusion: Minimizing opioid consumption may be achieved by avoiding tourniquet use in paediatric patients with lower leg procedures. In non-anaemic paediatric patients, it is reasonably risk-free to perform these surgeries without the use of tourniquet to decrease opioid dependence in the post-operative period. Level of evidence: III